The promoter of the white spot syndrome virus immediate-early gene WSSV108 is activated by the cellular KLF transcription factor. Issue 1 (March 2015) - Liu, Wang-Jing; Lo, Chu-Fang; Kou, Guang-Hsiung; Leu, Jiann-Horng; Lai, Ying-Jang; Chang, Li-Kwan; Chang, Yun-Shiang
Highlights WSSV108 has high expression levels throughout the WSSV infection cycle. WSSV108 is likely to act as a transcriptional factor. WSSV108 promoter has a Krüppel-like factor (KLF) binding site. Shrimp KLF plays a major role in WSSV108 promoter activity. Silencing of KLF in L. vannamei reduces WSSV108 expression and WSSV replication.